LEARNING DESIGN OF PROBLEM SOLVING MODEL ON THE CONCEPT OF HYDROCARBON ORIENTED HIGH-LEVEL THINKING ABILITY - Rostiawati; Neneng Windayani; Riri Aisyah (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to describe the learning design of the problem solving model on the hydrocarbon concept oriented to higher order thinking skills and to analyze the results of the validation test of learning tools in the form of lesson plans (RPP), worksheets (LK) and evaluation questions. This research method uses the Design Based Research (DBR) method with three stages, namely Analysis, Design, Development. The plan for implementing the developed hydrocarbon material learning contains steps in problem solving learning design. The results of the validation test show that the learning device in the form of a lesson plan developed is declared valid with a value of 0.93 in the valid category, so that the problem solving model of learning design can be used in chemistrylearning.